(untitled) (KULT_online, 2011)
This volume, edited by Gerhard Rupp, Jan Boelmann and Daniela Frickel, contains the proceedings of a graduate conference at Ruhr University Bochum in 2010. It is the second volume of the series "Leseforschung" (Research in Reading) and presents a versatile insight into current work by young German didactic researchers: the contributions extrapolate on new aspects and take a sidelong glance at strange ones, while also paying attention to the basics. In this book you can find theoretical work as well as concrete classroom research, intervention studies, and diagnostic procedures. It is an interdisciplinary anthology which contains studies of German literature, didactics, and sociology in addition to pedagogy- and psychology-based studies.